Accidental hypothermia: characteristics, outcomes, and prognostic factors—A nationwide observational study in Japan (Hypothermia study 2018 and 2019). Issue 1 (17th September 2021) - Takauji, Shuhei; Hifumi, Toru; Saijo, Yasuaki; Yokobori, Shoji; Kanda, Jun; Kondo, Yutaka; Hayashida, Kei; Shimazaki, Junya; Moriya, Takashi; Yagi, Masaharu; Yamaguchi, Junko; Okada, Yohei; et al.
Abstract : Aim: This study describes the clinical characteristics and outcomes as well as the prognostic factors of patients with accidental hypothermia (AH) using Japan's nationwide registry data. Methods: The Hypothermia study 2018 and 2019, which included patients aged 18 years or older with a body temperature of 35°C or less, was a multicenter registry conducted at 87 and 89 institutions throughout Japan, with data collected from December 2018 to February 2019 and December 2019 to February 2020, respectively. Results: In total, 1363 patients were enrolled in the registry, of which 1194 were analyzed in this study. The median (interquartile range) age was 79 (68–87) years, and the median (interquartile range) body temperature at the emergency department was 30.8°C (28.4–33.6°C). Forty‐three percent of patients with AH had a mild condition, 35.2% moderate, and 21.9% severe. AH occurred in an indoor setting in 73.4% and was caused by acute medical illness in 49.3% of patients. A total of 101 (8.5%) patients suffered from cardiopulmonary arrest on arrival at the hospital. The overall 30‐day mortality rate was 24.5%, the median (interquartile range) intensive care unit stay was 4 (2–7) days, and the median (interquartile range) hospital stay was 13 (4–27) days. In the multivariable logistic analysis, the prognostic factors were age (≥75 years old), male, activities of daily living (needing total assistance), cause of AH (trauma, alcohol), Glasgow Coma Scale score, and potassium level (>5.5 mEq/L). Conclusion: The mortality rate of AH was 24.5% in Japan. The prognostic factors developed in this study may be useful for the early prediction, prevention, and awareness of severe AH. Abstract : The overall mortality rate of accidental hypothermia (AH) in this study was 24.5%, and the poor prognostic factors of patients with AH included an older age (≥75 years old), a male sex, activities of daily living (needing total assistance), a low Glasgow Coma Scale score, and a high potassium level. By contrast, hypothermia caused by trauma and the highly intoxicated condition of the patient at presentation to the hospital were good prognostic factors.